The effect of cooperative learning with student Facilitator and explaining (sfae) model on students’ Willingness to speak up - Witarsa, Fauzi Indra (Universitas Pendidikan Indonesia, 2017)
This present study was aimed at investigating the influence of cooperative learning withSFAE model on triggering students to speak up when learning social science subject at JuniorHigh School of 2 Lembang. The research employed quasi experimental study with non-equivalent control group design as well as pre- and post- giving treatment at 7H class as theexperimental group, while 7I as the controlled group. The sample of the research was chosenby using purposive sample. One of the data gathering was a closed questionnaire thatinquired students’ willingness to speak up. The data were analyzed quantitatively by using t-test. The study revealed that the results between pre- and post- giving treatment gained by theexperimental group showed significant difference. Whereas, the scores achieved in pre- andpost- the treatment by the controlled group were alike or the scores had no improvement.Consequently, it can be concluded that the use of cooperative learning with student facilitatorand explaining (SFAE) model affected significantly on students’ willingness to speak upwhen learning social science subject. yang berpengaruh terhadap sikap keberanian berbicarasiswa dalam pembelajaran IPS.